Spaces of generalized operators with bounded projection trace - Hrushka, Ya. I. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We construct a theory of Banach spaces of "generalized" operators with bounded projection trace over the given Hilbert space. This theory can be efficient in investigating evolution problems for quantum systems with infinite number of particles.